Green field development in the context of biological activity. The anatomy of a new paragraph in the Hungarian Building Law - Jámbor, Imre; Szilágyi, Kinga (4D Journal of Landscape Architecture and Garden Art, 2006)
The increase of the built-up areas in the Hungarian urban regions in the past decade does not consider the loss of the active biological areas. In the interest of the reduction of environmental load, caused by urban development, and mainly by “green area” investments the new Building Law is to contain a new paragraph (8/A.§) on new institutional tools for urban development and planning to prevent or ease the loss of biological active surface.
Keywords: green field development; building law